Financial and Fiscal Instruments for Catastrophe Risk Management : Addressing Losses From Flood Hazards In Central Europe (Poland, Czech Republic, Hungary and Slovakia) - Pollner, John D. (World Bank, 2012)
This report addresses the large flood exposures of Central Europe and proposes efficient financial and risk transfer mechanisms to mitigate fiscal losses from natural catastrophes.. The report is primarily addressed to the governments of the region which should build into their fiscal planning, the necessary contingent funding mechanisms, based on their exposures. While there exist pan-European mechanisms such as the EU Solidarity Fund to help EU members fund mega disasters, these only kick in at extremely high loss levels. Given these issues, the Governments of the V-4 countries should consider it a priority to set up risk transfer mechanisms to reduce fiscal volatility following natural catastrophes. The private sector insurance markets in the V-4 countries appear adequate and reflect rather high levels of penetration in the economy and in the housing sector. Economic and fiscal analyses based on global data also show that countries with insurance mechanisms and markets show a stronger GDP recovery path and lower fiscal deficits following a disaster. However, the V-4 countries, having a common hazard of flood, are in a unique position to develop highly cost effective flood insurance mechanisms. As countries in general are more concerned with supplemental fiscal resources rather than individual property losses, the governments of the V-4 countries can consider parametric style contracts. Nevertheless, risk transfer or insurance mechanisms are not the only types that need to be considered. The analysis in this report is meant to show, besides the financial mechanisms that would be beneficial for risk management, what large catastrophe exposures exist and their relation to government finances and macroeconomic measures. Following a final phase of feasibility analysis and market testing, the V-4 countries should thus consider establishing a multi-country insurance pool to provide fast emergency funding after disasters.